Gayatri Rajapatni's Leadership Strategy as a Revolutionary Woman Designer of the Majapahit Empire's Vision - Maharani, Devy Adillia; Badar, Ali (Universitas Islam Negeri Sumatera Utara, 2025)
Modern societies view women as equal to men, especially in government. conversely, societies with traditional stigmas view women as having power only in the domestic sphere. Historically, Javanese women, particularly in the ancient Javanese era, held a strategic position in shaping government policy. This is evident in the presence of Gayatri Rajapatni in the Majapahit Kingdom. Gayatri served as an advisor to the king and a policy maker, although she was not legally the queen. This study aims to determine the leadership strategy of Gayatri Rajapatni, a figure behind the success of Majapahit. This study used historical research methods and resulted in an analysis of Gayatri Rajapatni's leadership strategy in building the Majapahit Empire. The author concludes that Gayatri Rajapatni employed various leadership strategies to implement her vision for Majapahit's glory, namely by developing tactics and leadership patterns inherited from her father (Kertanegara).